Gamification, collaborative learning and transversal competences: analysis of academic performance and students’ perceptions - Cecilia Latorre-Cosculluela; Verónica Sierra-Sánchez; Sandra Vázquez-Toledo (Smart Learning Environments)
Abstract The importance and benefits of teamwork in the university context have been widely recognized in recent decades. However, there is little evidence that analyzes the effects of the combination of collaborative learning strategies and gamification methodologies for the improvement of transversal skills and academic performance. In this sense, in this study an intervention program was carried out in the university classroom that alternated the use of technology, gamification (through the use of the ClassDojo platform) and collaborative learning to improve the development of transversal skills. More specifically, the objective was to analyze the academic performance and qualitative perceptions of university students after the application of a gamified educational approach. A mixed research methodology was used with quantitative and qualitative techniques combining descriptive, correlational and linear regression analysis and an interview was administered to the 117 students involved in the experience. The results obtained indicated that the application of the program produced improvements on the development of transversal competences and on the academic performance of university students. In addition, the qualitative analysis of the perceptions allowed us to conclude that this program that combines gamification with collaborative learning received a positive evaluation by the students regarding different variables such as the applicability of gamification for the improvement of softskills, the benefits on the teaching–learning process and other factors that influence motivation before the use of gamification techniques in learning.